Cam Jansen and the first day of school mystery - Adler, David A.; Natti, Susanna (New York : Viking, 2002)
On her first day of fifth grade, Cam Jansen uses her photographic memory to help the police find a car thief. Includes a memory game.
edited hb 2015-06-16
Keywords: Jansen, Cam (Fictitious character) -- Fiction; First day of school -- Fiction; Schools -- Fiction; Memory -- Fiction; Mystery and detective stories